The Influence Of Corporate Social Responsibility, Profitability, Capital Structure On Company Value - Ardian Alfiadin; Dwi Ermayanti Susilo (GOVERNORS, 2022)
This study aims to determine the effect of Corporate Social Responsibility, Profitability, and Capital Structure on Company Value in the current Covid 19 pandemic era. The problem sttement in this study are as follows: 1) Does Corporate Social Responsibility (CSR) have a positive effect on Pharmaceutical Companies Value registered on IDX for the period 2017-2021, 2. Does profotability has positife influence to Pharmaceutical  Companies value registered on BEI on periode 2017-2021, 3) Does Capital Structure have a positive effect on Pharmaceutical Companies Value registered on IDX for the period 2017-2021, 4) Does Corporate Social Responsibility (CSR), Profitability, and Capital Structure have a positive effect on Company Value in Pharmaceutical companies registered on IDX for the period 2017-2021.This research uses descriptive quantitative research. The population and sample in this study are pharmaceutical companies listed on the Indonesia Stock Exchange for the period 2017-2021. The data used is secondary data on annual financial reports on the Indonesia Stock Exchange. This study uses data analysis techniques such as multiple regression analysis and SPSS as a tool to process and test data. The results of this study indicate that partially CSR has no significant effect, ROE has a significant effect and DER has no significant effect on firm value. Meanwhile, simultaneously CSR, ROE, and DER have a significant effect on firm value.